Performance of nested-RT-PCR assays for Zika and Dengue detection (Acta Scientiarum. Biological Sciences, 2025)
Arboviruses represent a public health problem in developing countries. Accurate diagnosis has been challenging in Dengue virus endemic countries, especially since the introduction of the Zika and Chikungunya viruses. The aim of this study was to determine the sensitivity and specificity of nested Reverse Transcription Polymerase Chain Reaction (nested-RT-PCR) in a Zika virus epidemic setting. A total of 179 serum samples from patients with acute febrile syndrome reported between 2015 and 2016 were analyzed by nested-RT-PCR using real-time PCR (RT-qPCR) as reference test. The nested-RT-PCR assay demonstrated moderate agreement (kappa = 0.49) in identifying Dengue virus, resulting in 40.00% positive and 99.42% negative predictive values. Zika virus detection showed fair agreement (kappa = 0.29), with 100% positive and 92.61% negative predictive values (p-value < 0.05, Fisher’s exact test). The diagnostic accuracy rates for the nested-RT-PCR assays were 97.76% for Dengue virus and 92.74% for Zika virus. The sensitivity and specificity of nested-RTâ€’PCR for detecting Dengue virus were 66.66% and 98.29%, respectively; Zika virus RNA detection had 18.75% sensitivity and 100% specificity with the nested-RT-PCR protocol. In conclusion, the RT-qPCR assay is the most reliable method for diagnosing suspected cases of dengue and zika fever, providing adequate, timely and accurate laboratory responses to the proper management of patients, despite the high overall analytical accuracy of nested-RT-PCR.